MON-LB008 PD-L1 Expression in Normal Endocrine Tissues - Pollack, Rena (J Endocr Soc, 2019)
Introduction: Immune checkpoint inhibitor (ICI) therapy, including cytotoxic T-lymphocyte-associated protein 4 (CLTA-4) and programmed cell death 1 (PD-1) inhibitors, is revolutionizing cancer treatment. However, these agents are associated with immune-related adverse events (irAEs), most commonly endocrine-related. Hypophysitis, thyroid dysfunction, insulin-deficient diabetes mellitus and primary adrenal insufficiency have been reported as irAEs due ICI therapy. The precise mechanisms underlying these endocrine irAEs remain to be elucidated. Aim: In this study, we evaluated patterns of programmed cell death ligand 1 (PD-L1) expression in normal endocrine tissues to determine whether increased expression may explain the predilection of endocrinopathies in patients treated with PD-1 inhibitors. Methods: Immunohistochemical (IHC) analysis using the Ventana 22C3 PD-L1 IHC platform was performed on normal FFPE endocrine tissue samples stored in our hospital pathology tissue archive. Results: Five samples from each organ including pituitary, thyroid, parathyroid, adrenal and pancreas were examined. Focal membranous PD-L1 positivity was noted in the normal pituitary tissues, but was negative in normal thyroid, parathyroid, adrenal and pancreatic tissues. Conclusions: Majority of normal endocrine tissues do not demonstrate increased PD-L1 expression. Our limited data so far does not support the hypothesis that increased PD-L1 expression in endocrine tissues is associated with the endocrine irAEs following anti PD-1 therapy. The increased predilection of endocrinopathies in patients treated with anti PD-1 inhibitors seems to be via alternate pathways. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.